Hubungan Kualitas Air Minum dan Kebiasaan Makan/Minum di Luar Rumah dengan Terjadinya Demam Tifoid pada Pasien Rawat Inap di RSUD Kota Kendari - Zida Maulina Aini (Halu Oleo University, 2019)
ABSTRACT Background: Typhoid fever is a disease which arouse from the infection from Salmonella Typhi superbug through either the contaminated food or drink.It is recorded in 2016, Typhoid fever belongs to the highest ten contagious diseases in Southeast Sulawesi and comes in fifth with the cases of 4.641 sufferers. Purpose: This research study is aimed to know the bearing of quality of water, source of hygienic water and outdoor eating/drinking habit and the cause of typhoid fever to inpatients at Regional General Hospital in Kendari. Method: This research is an observational- descriptive study with a cross sectional design. 38 people of all the inpatients who had more than three days fever were used to be the total of sampling of this research. The instrument of this study is in the form of questioner. The Chi-square trial formula at significant rates (α = 0.05) was used in this research to analyze the data. Result: It is found that out of the 38 respondents, those who measure up for the quality of water are 16 respondents while who do not are 22 respondents with the value of (p=0,544). Meanwhile, there are 20 respondents of good outdoor eating or drinking habit and 18 respondents of the bad one with the value of (p=0,049).Keyword: typhoid fever, outdoor eating/drinking habit, quality of water